ANALISIS KECELAKAAN KERJA DENGAN MENGGUNAKAN METODE HAZOP (HAZARD AND OPERABILITY STUDY), WHAT IF/CHECKLIST DAN JSA (JOB SAFETY ANALYSIS) PADA PT XYZ - Devi Pusparina (2022)
PT XYZ is a company engaged in food. This company is one of the largest companies in producing instant noodles, because it is one of the large companies, it is important for companies to implement Occupational Health and Safety (K₃). After doing research at PT XYZ, it turns out that there are still many work accidents at several points in the production area. The potential hazards found were analyzed into 3 methods, namely HAZOP (Hazard and Operability Study), What If/Checklist and JSA (Job Safety Analysis) in the hazop method the hazard findings were grouped in 23 work areas after which the likelihood and severity values were calculated to get the risk level value. and validity and reliability tests were conducted to ensure that the data taken were based on research conducted using the SPSS application. The next method is What If/Checklist which is done by distributing questionnaires which will later determine the risk priority. The last is the JSA method is slightly different from the two previous methods because the risk assessment is assessed from the projects being worked on, not from the work that is done every day. Improvements in the jsa method will later be made safely work permit or form before doing a project or work.